PELATIHAN PEMBUATAN SILASE GAMAL SEBAGAI PAKAN KAMBING - Ardika, I.N.; Melati, N.P.Y.; Warmadewi, D.A.; Sumadi, I.K.; Lindawati, S.A. (Buletin Udayana Mengabdi, 2024)
Yehembang Kauh Village is located at an altitude of 0 – 500 m above sea level with relatively moderate rainfall. The economic structure of the community is still agricultural in nature with the main commodities produced by the residents of Yehembang Kauh village being cocoa, coconut, cloves and rice farmers producing rice and secondary crops. Apart from that, people also depend on the livestock sector for their livelihood, with types of domesticated livestock such as; goats, Bali cattle and poultry so that the provision of forage sources is very necessary to meet the needs of livestock, especially goats. The problems faced in providing forage are fluctuating forage production in the rainy season and dry season, limited land for planting forage because the available land is prioritized for food crops and plantations. The aim of this service activity is to assist livestock farming groups in providing ruminant feed in the dry season through silage making technology. The activity method is carried out through counseling, discussion and practice of making gamal silage so that it can be used as a feed stock during the dry season. Based on the results of the evaluation of observations of the physical quality of the silage that has been made, it can be seen that the characteristics of this gamal-based silage have a green-brown color with a score of 3, a crumbly/soft texture with a score of 3, a sour aroma with a score of 3 and a pH of 4.5 which is categorized as good and no mold grows. Keywords: feed stock, fermentation, silage, gamal, goats.